Implication of soil-structure interaction on deteriorate existing frames in Penang - Md. Kassim, Tahara Ramadzan; A. Majid, Taksiah (IOP Publishing Ltd, 2020)
Soil-structure interaction (SSI) is often disregarded to reduce difficulties in analyses. Thus, most of analyses adopted rigid foundation despite ignoring SSI could lead to inaccurate response. Current study investigates the influence of SSI on low-to medium-rise existing frames considering non-seismic loading. A multichannel analysis of surface wave (MASW) is performed at several locations in Penang to obtain shear wave velocity of local site conditions. The frames are modelled with rigid and flexible (soil flexibility) and analyzed using nonlinear static analysis. Each of the frames is subjected with seismic zone factor to predict the seismic response using Acceleration-Displacement Response Spectra (ADRS) concept. A flexible base elongated the period mainly under soft soil (soil E), increasing by up to 6.27%, 9.44%, and 4.12% for 3-, 6-, and 16-story frames, respectively. The frames that considered SSI experienced degradation of their capacity curve, strength, and stiffness. Under a dissimilar seismic zone factor, low-story frames achieved high demand, whereas high-story frames delivered maximum displacement is observed.